Kwadrat, koło, trójkąt - Madejski, Jerzy (Er(r)go. Teoria - Literatura - Kultura, 2001)
This review essay offers an in-depth discussion of Aleksandra Czermińska's work Autobiograficzny trójkąt. Świadectwo, wyznanie i wyzwanie.